2016
DOI: 10.1515/cpe-2016-0018
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of adsorption of Cd(II) and Pb(II) ions on pure and chemically modified fly ashes

Abstract: The study investigates chemical modifications of coal fly ash (FA) treated with HCl or NH4HCO3 or NaOH or Na2edta, based on the research conducted to examine the behaviour of Cd(II) and Pb(II) ions adsorbed from water solution on treated fly ash. In laboratory tests, the equilibrium and kinetics were examined applying various temperatures (293 - 333 K) and pH (2 - 11) values. The maximum Cd(II) and Pb(II) ions adsorption capacity obtained at 293 K, pH 9 and mixing time 2 h from the Langmuir model can be groupe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 36 publications
2
23
0
Order By: Relevance
“…(2) and (3) are frequently used (Ho and Wang, 2004;Ho, 2006;Sočo and Kalembkiewicz, 2016). When the adsorption mechanism is mainly physical, the kinetics is usually described with Eq.…”
Section: Sorption Kineticsmentioning
confidence: 99%
“…(2) and (3) are frequently used (Ho and Wang, 2004;Ho, 2006;Sočo and Kalembkiewicz, 2016). When the adsorption mechanism is mainly physical, the kinetics is usually described with Eq.…”
Section: Sorption Kineticsmentioning
confidence: 99%
“…A combined process of precipitation (Cr(OH) 3 , Cd(OH) 2 ) and adsorption (Cr(OH) 4 − ) at pH > 9 was observed (Figure 6a,b). The order of affinity based on the amount of sorbate removal is as follows, with a hydrated ion radius: Cr(III) (4.13 Å) > Cd(II) (4.26 Å) > CV (above 40 Å) [37]. It was found that the sorption process predominates between positively charged CV molecules and the negatively charged silanol group.…”
Section: Influence Of Phmentioning
confidence: 97%
“…Then, the mixtures were subjected to agitation at pH 9.0 for 1.5 h (see Section 3.4.1). The method was described according to the work in [37].…”
Section: Sorption Of Analytesmentioning
confidence: 99%
“…The process of precipitation (Cd(OH) 2 ) and adsorption (CdOH + ) at pH 6-9 was observed. Moreover, at pH>9 it was also the combined process of precipitation (Cd(OH) 2 ) and adsorption (Cd(OH) 3ˉ) [19]. When the pH is higher than 7 the aggregation of RB decreases because excessive OHˉ competes with COOˉ in binding with -N + and the lactone form of RB is formed (Fig.…”
Section: Influence Of Phmentioning
confidence: 99%
“…The selectivity sequence of metal and dye is generally explained on the basis of the properties of ion size, such as the smallest hydrated ionic radii (4.26Å) and RB cation weight. It is possible that the Cd(II) ions with fewer weakly bonded water molecules tend to move faster to potential adsorption sites on FA-HDTMABr, compared to the RB cations with higher ionic radii [19]. Langmuir isotherm is often used to describe adsorption of solutes from liquid solutions and the model assumes monolayer adsorption onto a homogeneous surface with a finite number of identical sites [27,28].…”
Section: Equilibrium Studiesmentioning
confidence: 99%